Mediating effects of social support between telework and well-being: protocol for a systematic review - Guillaume Fernandez; Mattia Vacchiano; Javier Fernandez-Garcia (BMJ Open)
Introduction Research on telework has grown dramatically in recent years, leading to a fragmented set of findings on its effect on workers’ well-being. One of the most studied social mechanisms concerns how telework alters the transmission of social support between family members and coworkers, which turns out to be a mediating factor between teleworking and well-being. This research contributes to the understanding of this issue by analysing the existing evidence on the effect of telework on social support and well-being before, during and after the pandemic.Methods and analysis Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we will systematically synthesise evidence about the mediating effect of social support in the relation between telework and well-being. Three databases will be used to search the literature addressing this issue: Social Sciences Citation Index (Web of Science), Sociological Abstracts (PROQUEST) and SocINDEX with full text (EBSCOhost). Quantitative and qualitative studies published in peer-reviewed journals, in English and French, from January 2000 to June 2024 will be included in this systematic review. Double screening procedure with data quality assessments will be carried out by three researchers independently for up to 20% of the studies. Conflicts will be resolved for the completion of the remaining 80% of the studies by two researchers. The literature review aims to systematise the links between telework, social support and well-being by identifying the different dimensions and mechanisms that link these three aspects. The information will be synthesised using Qualitative Content Analysis. Additional analysis will be performed using the term frequency–inverse document frequency (TF-IDF).Ethics and dissemination This is a protocol for a systematic review. Aggregate published data is used; therefore, no ethical approval is required. The results of the review will be disseminated through peer-reviewed journals and presentations at conferences.PROSPERO registration number CRD42024554590.